RELAS I SOSIAL KELAYAN TUNANETRA DI PANTI SOSIAL BINA N ETRA TUAH SAKATO PADANG (Deskriptif Kualitatif) - WINNI FERAH (Universitas Negeri Padang, 2015)
ABSTRACT This research discussed about the social relation. This researc h was intended to describe the process of social relation in the preparation class covering sveral indicators such as the process, obstracles, and the efforts done. This research was conducted at PSBN Tuah Sakato Padang. This research applied descriptive qualitative approach focusing on the process of social relation for the clients with visual impairment. The subject of the research was the head of the institution, the teachers handling skill classes, the subject teachers, the Guidance and and Counseling teachers, the psychology teachers, and the clients in the preparation class. The data were collected through observation, interview and documentation study. The results of the research showed that the social relation in the preparation class existed in all of subject, while the implementation was more significant in mobility orientation subject. The guidance was given only 3 hours in a single meeting a week. The evaluation was done once in three months or four times in a year. The learning materials were taught repeatedly so that the clients had deep understanding on them. The clients living in the house were those who neither went to regular nor to special school previously, and they had low intelligence. In the future, it was expected to the intructors and the institution fellows to provide more times to the clients to get intensely guidance in mobility orientation subject whose materials required the students to do a lot of practice.